Literasi Keuangan Terhadap Perilaku Pengelolaan Keuangan Pada Mahasiswa Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa - Teguh Erawati; Naomi Peda Lado (Jurnal Literasi Akuntansi, 2024)
Purpose: The purpose of this study was to To examine how financial literacy affects financial management behavior in students. Method: In this study, researchers took a sample of students of the Faculty of Economics, Sarjanawiyata Tamansiswa University Yogyakarta class of 2019-2022. The number of samples in this study were 105 students. This research method uses a questionnaire, then processed and analyzed with SPSS version 25. Finding: Financial literacy has a significant positive effect on financial management behavior in students because students with a high level of financial literacy tend to make smarter financial decisions in financial management and also financial literacy provides the knowledge base needed for decision making in financial management behavior in students. Novelty: In previous studies, researchers were more financial literacy leads to family financial literacy while current research is more directed at student financial literacy. Keywords: Financial Literacy, Financial Management Behavior.